Concrete Proposals Outlining Forest Management and Afforestation in River Valley Projects - Prasad, B. N. (Indian Forester, 1958)
Historical background has been given showing the advances made up to the last Hirakud Seminar. While the Roorkee Seminar refused to allocate any fund for soil conservation measures from the project estimate, the Hirakud Seminar recommended 2 to 5 per cent of the River Valley Project funds for the purpose. Grounds have been given for considering soil and water conservation as an integral and essential part of any River Valley Project. It has been shown that merely constructing dams will result in more frequent and devastating floods after some time if the forests in the catchment are not specially managed and protected. Concrete proposals have been outlined for achieving this purpose. Special attention may be given to the resolution proposed at the end of this paper.